Exploring perception of healthy aging: a qualitative study - Deotale, Vipul; Telang, Namrata; Mohanty, Manjeet; Desai, Rohini; Golawar, Sameer; Narlawar, Uday (International Journal Of Community Medicine And Public Health, 2025)
Background: Healthy aging is an emerging and vital topic in India due to the country’s significant demographic shift. According to the United Nations, India had over 93.3 million persons in the 60+ age group by the end of the first decade of this century. Healthy aging involves more than just the absence of disease. To better understand the complexities of healthy aging in India, a qualitative exploration of the topic is necessary so this study explores perceptions related to healthy aging in the elderly. Methods: People aged 60 years and over, living in the community in the city of central India were selected conveniently and data was collected in various municipal corporation gardens after explaining the purpose of the study and if they were willing, to participate in the study were enrolled, 24 participants out which 66.6% and 33.3% male and female respectively and the mean age of participant were 64 year were enrolled in the study and divided into 3 focus groups, each focus group contained 8 people and each focus group discussion lasted for approximately 1 hour with probing questions until saturation, The focus groups were audio-recorded. The participants were asked to share their opinions regarding healthy aging. Results: The 5 main themes arise consisting of free from illness, social engagement, healthy lifestyle, financial stability, and self-sufficiency. Conclusions: In this study the elderly participant defined healthy aging as reaching a state of well-being that includes Free from illness, social engagement, healthy lifestyle, financial stability, and self-sufficiency.